2022
DOI: 10.1177/2473974x221083092
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Disparities in the Treatment of Borderline/Mild Hearing Loss in the United States

Abstract: To investigate disparities in hearing aid use across the life span for borderline/mild hearing loss, a cross-sectional epidemiologic study in the National Health and Nutrition Examination Survey was conducted. Multivariable logistic regressions controlling for hearing level analyzed the association between hearing aid use and age in borderline/mild hearing loss. Age was grouped into quartiles. Of 2470 subjects, 2.0% (n = 50) were <25 years old; 12.0% (n = 297), 25 to 49 years; 65.5% (n = 1618), 50 to 74 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The observation that older adults were disproportionally affected requires particular attention, as these patients may be less likely to seek care in the COVID-19 era (9). Moreover, these findings compound findings from other groups who have demonstrated that Medicare-aged adults experience greater delays in referral for cochlear implantation (10,11), receive less overall treatment (12,13), and display less awareness of CIs as a treatment option-all despite the greater prevalence of more significant hearing loss in this demographic (14). Finally, the observation that elderly adults were disproportionally affected is also compounded by the sequelae of social isolation and difficulty communicating when masks are worn.…”
Section: Discussionmentioning
confidence: 70%
“…The observation that older adults were disproportionally affected requires particular attention, as these patients may be less likely to seek care in the COVID-19 era (9). Moreover, these findings compound findings from other groups who have demonstrated that Medicare-aged adults experience greater delays in referral for cochlear implantation (10,11), receive less overall treatment (12,13), and display less awareness of CIs as a treatment option-all despite the greater prevalence of more significant hearing loss in this demographic (14). Finally, the observation that elderly adults were disproportionally affected is also compounded by the sequelae of social isolation and difficulty communicating when masks are worn.…”
Section: Discussionmentioning
confidence: 70%
“…The cognitive relationship is present even for a minimal level of HL 30,40‐42 . Disturbingly, even though older adults are at risk for many of these disorders, their HL may be less likely to be treated than younger individuals 4 . These data contribute to the growing field of the potential impact of HL beyond audition and the importance of equitable treatment in often overlooked groups.…”
Section: Discussionmentioning
confidence: 95%
“…Hearing loss (HL) is the third most common chronic physical condition in US adults, 1 and yet only 11% who have at least unilateral HL and subjective moderate difficulty hearing use hearing aids 2,3 . This represents a significant proportion of the population at risk for the negative sequelae associated with HL 4 . Many studies have recently shown strong associations between HL and numerous deleterious medical comorbidities, including depression, cognitive decline, dementia, and most recently, serious mental illness 5‐13 .…”
mentioning
confidence: 99%
“…Some organizations, such as the American Speech-Language-Hearing Association, include a slight HL category of 16 to 25 dB (36). It has been proposed that implicit ageism, rather than rational biological evidence, underlies the reason for different definitions of HL in children versus adults (37). For example, in both children and adults, minimal levels of HL are similarly associated with worse cognition (20,38).…”
Section: Discussionmentioning
confidence: 99%